CONTROL OF THE SPATIAL STRUCTURE IN PRESCHOOL CHILDREN - N. Dimitrova (Trakia Journal of Sciences)
In early childhood, most motor tasks are based on kinematic structure, as children assimilate motor culture in the way of imitation actions. Substantial development during this period also suffers from the controlling system, as a major problem is the differentiation of the effects of development on the one hand and education on the other. According to our working hypothesis, we assume that the educational process, both in primary school and pre-school age, should focus not on physical qualities but on improving the functioning of the controlling (external and internal circle) system. The aim of this study is to quantify some basic parameters for the management of spatial biomechanical characteristics in the earliest childhood. The selected test motor tasks registered regional and global accuracy assessment mutual location and the reachable area between cinematic pairs.